Management of ocular surface squamous neoplasia: Bowman Club Lecture 2021. Issue 1 (27th July 2021) - Alvarez, Osmel Peter; Zein, Mike; Galor, Anat; Karp, Carol L
Abstract : The gold-standard treatment for ocular surface squamous neoplasia (OSSN) has traditionally been surgical excision with wide margins and a no-touch technique. However, surgery may be associated with several unfavourable sequelae, as well as significant recurrence rates if margins are positive. In recent years, topical chemotherapy with 5-fluorouracil, interferon α−2b and mitomycin C have emerged as valuable agents capable of effectively treating OSSN with varying adverse effects. These medical treatment options usually present additional costs to the patient but can allow patients to avoid surgery with fewer long-term effects. Anterior segment high-resolution optical coherence tomography is an excellent tool for diagnosing and monitoring OSSN and can be a useful aid for both surgical and medical treatments of OSSN.